2016
DOI: 10.1136/vr.103533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amoxicillin, ceftiofur, doxycycline, tiamulin and tulathromycin on pig humoral immune responses induced by erysipelas vaccination

Abstract: It addition to their antimicrobial properties, antibiotics can influence the host immune system (modulation of cytokine secretion, antibody production and T-cell proliferation). In the present study, the authors studied the effects of therapeutic doses of amoxicillin (AMX), ceftiofur (CEF), doxycycline (DOXY), tiamulin (TIAM) and tulathromycin (TUL) on the postvaccinal immune response after pigs had been vaccinated against erysipelas. Because humoral immunity is considered as the most important in the protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 19 publications
(32 reference statements)
4
18
2
1
Order By: Relevance
“…This may have an unfavourable impact on the immune system response to infection and/or vaccination. This assumption is in accordance with the outcome of earlier studies conducted by Pomorska-Mól et al (21,22) in which therapeutic doses of ceftiofur during vaccination impaired post-vaccinal immune responses in pigs. The negative effect of ceftiofur, florfenicol, and enrofloxacin on B and T cell subsets was also found in another study on chicks, where results were similar to the present study (6).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may have an unfavourable impact on the immune system response to infection and/or vaccination. This assumption is in accordance with the outcome of earlier studies conducted by Pomorska-Mól et al (21,22) in which therapeutic doses of ceftiofur during vaccination impaired post-vaccinal immune responses in pigs. The negative effect of ceftiofur, florfenicol, and enrofloxacin on B and T cell subsets was also found in another study on chicks, where results were similar to the present study (6).…”
Section: Discussionsupporting
confidence: 92%
“…Evidence of the proapoptotic effect of tulathromycin on leukocytes, enhanced efferocytosis process, and inhibition of LTB4 production has also been noted in A. pleuropneumoniaechallenged pigs (11). Beyond the pro-resolution effects, it has also been shown that tulathromycin promotes the post-vaccinal humoral immune response in pigs vaccinated against erysipelas (22).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a similar study by a different group, using 105 8week old pigs, it was found that vaccination of pigs against erysipelas in the presence of antibiotics may result in a decrease (ceftiofur, doxycycline, tiamulin) or enhancement (amoxillin, tulathromycin) in the production of specific antibodies against Erysipelothrix spp. (106). In contrast, the use of ginseng as a coadjuvant has been shown to improve the antibody response of vaccination (109).…”
Section: Currently Available Commercial Vaccinesmentioning
confidence: 99%
“…In experimentally vaccinated pigs, IgM and IgG responses can be demonstrated between 7 and 21 days post vaccination (136)(137)(138)(139)(140). A study using conventional pigs found that vaccination of pigs with a commercial inactivated vaccine in the presence of antibiotics may result in a decrease (ceftiofur, doxycycline, tiamulin) or enhancement (amoxicillin, tulathromycin) in the production of specific antibodies as measured by a commercially available E. rhusiopathiae ELISA (106). During assessment of a large vaccination program in various marine mammals by a modified FMIA, a mean 311-fold increase in the IgG antibody index was detected 14 days after the first booster vaccination (112).…”
Section: Immunological Basis or Correlates Of Protection For Existingmentioning
confidence: 99%